First Images of a Three-Layer Compton Telescope Prototype for Treatment Monitoring in Hadron Therapy - Llosá, Gabriela; Trovato, Marco; Barrio, John; Etxebeste, Ane; Muñoz, Enrique; Lacasta, Carlos; Oliver, Josep F.; Rafecas, Magdalena; Solaz, Carles; Solevi, Paola (Frontiers in Oncology, 2016)
A Compton telescope for dose monitoring in hadron therapy is under development at IFIC. The system consists of three layers of LaBr3 crystals coupled to silicon photomultiplier arrays. Na-22 sources have been successfully imaged reconstructing the data with an ML-EM code. Calibration and temperature stabilization are necessary for the prototype operation at low coincidence rates. A spatial resolution of 7.8 mm FWHM has been obtained in the first imaging tests.